Prognostic implications of type 2 Diabetes Mellitus in heart failure with mildly reduced ejection fraction - Schupp, Tobias; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Lau, Felix; Reinhardt, Marielen; Abel, Noah; Schmitt, Alexander; Forner, Jan; Ayasse, Niklas; Bertsch, Thomas; Akin, Muharrem; Akın, Ibrahim; et al. (Journal of Clinical Medicine, 2024)
Background: Data regarding the characterization and outcomes of diabetics with heart failure with a mildly reduced ejection fraction (HFmrEF) is scarce. This study investigates the prevalence and prognostic impact of type 2 diabetes in patients with HFmrEF. Methods: Consecutive patients with HFmrEF (i.e., left ventricular ejection fraction 41-49% and signs and/or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. Patients with type 2 diabetes (dia-betics) were compared to patients without (i.e., non-diabetics). The primary endpoint was all-cause mortality at 30 months. Statistical analyses included Kaplan-Meier, multivariable Cox regression analyses and propensity score matching. Results: A total of 2169 patients with HFmrEF were included. The overall prevalence of type 2 diabetes was 36%. Diabetics had an increased risk of 30-months all-cause mortality (35.8% vs. 28.6%; HR = 1.273; 95% CI 1.092-1.483; p = 0.002), which was confirmed after multivariable adjustment (HR = 1.234; 95% CI 1.030-1.479; p = 0.022) and propensity score matching (HR = 1.265; 95% CI 1.018-1.572; p = 0.034). Diabetics had a higher risk of HF-related rehospitalization (17.8% vs. 10.7%; HR = 1.714; 95% CI 1.355-2.169; p = 0.001). Finally, the risk of all-cause mortality was increased in diabetics treated with insulin (40.7% vs. 33.1%; log-rank p = 0.029), whereas other anti-diabetic pharmacotherapies had no prognostic impact in HFmrEF. Conclusions: Type 2 diabetes is common and independently associated with adverse long-term prognosis in patients with HFmrEF.
Veröffentlicht: 27. Januar 2024
Gesehen am 05.06.2024